Trajetórias da internacionalização da Universidade Pública: avaliação do Programa Ciência sem Fronteiras à luz da experiência da Universidade Federal do Ceará - Garcia, Márcia Monalisa de Morais Sousa (2020)
Internationalization has been a prominent theme in discussions around higher education in Brazil, especially with the creation of the Ciência sem Fronteiras Program -CsF (Science without Borders), launched by the Dilma Rousseff Government (2011-2016) and closed for undergraduate students during the Michel Temer Government (2016-2018). Based on the assumption that the Science without BordersProgram would have boosted the internationalization of the Federal University of Ceará (UFC), this evaluative research hadthe general objective of evaluating the CsF Program and its developments in the institutionalization of UFC internationalization. Tothis end, the intentions that guided the CsF were analyzed; the national and institutional political context in which the Program was implemented; the way CsF was implemented at UFC, as well as the meanings that the Program brought to the perception of its managers. To this end, this research was based on the perspective of in-depth evaluation, by Rodrigues (2008), founded onthe hermeneutic paradigm of Lejano (2012), which offered the necessary elements (content analysis, context analysis, analysis of theinstitutional trajectory and analysis of the temporal and territorial spectrum) to carry out a multidimensional assessmentof CsF at UFC. Methodologically, a qualitative research was carried out, with quantitative contributions, in addition to bibliographic, documental research and semi-structured interviews with the rectors, undergraduate deans, coordinator of international affairs and coordinators of nine undergraduate courses at the University, covering the implementation period of the Program. Throughthe analytical axes of in-depth evaluation (content analysis, context analysis, analysis of the institutional trajectory),with the analytical contributions of Lejano (2012), it was observed that, although the objectives of the CsF denote a technical-scientific characterization , the concept of internationalization that guides the Program is based on meeting market demands, as established by the WTO.However, contradictorily, the concept of internationalization based on solidarity, as established by UNESCO, appears in the trajectories of the CsF, in the case analyzed, institutionally, in the UFC.From the notions of coherence and topology of the institutions of Lejano (2012), there are distinct interpretations about the CSF in the UFC and its relationship with internationalization.The evaluative research and its results build indicators about the Program at the University by understanding the changes in political-institutional contexts and the perceptions of the managers, which affected and modified the trajectories of the CSF, evidencing contradictions resulting from disputes between different political projects of State and society, which circumscribe CsF and UFC internationalization.With that, it is concluded that, from the CsF, the internationalization took new paths in the UFC, revealing the contradictions and the field of disputes of interests existing in the institution and in the political and economic field, which presents the internationalization among the limits of solidarity and commercializationof education.